PERUBAHAN FUNGSI LAHAN DI MUARA SUNGAI TERHADAP PELESTARIAN SUMBER DAYA AIR - Putu Eryani, I Gusti Agung; Sinarta, I Nengah; Surayasa, I Nyoman (Bumi Lestari; Vol 14 No 1 (2014), 2014)
Bali has many rivers with river water discharge conditions is quite large and a lot of wasted at the mouth of the river in vain , because not all of the water used for agricultural needs and raw water . Current physical land in the mouth of the river has begun to change from agricultural land into building that support tourism in Bali This is in line with the development of tourism industry of small -scale tourism and large -scale tourism . In line with this condition, the problem is how the characteristics of the river mouth in Bali with the change in land use in the mouth of the river and how water resources management methods that go into the mouth of the river so that water resources be sustainably. Research methods that will be used is phenomenology . This is in accordance with the principle of preservation of objects that many studies related to water resources management system . The research process consists of two stages . Results obtained in the form of characteristics of the river , the river mouth morphology after land use change around the mouth of the river, based on secondary data ( reports of Bali Provincial Department of Public Works ) and research in the field ( primary data ) , this study uses the software as a tool of analysis . Karakteristik morphology Sowan estuaries ( Perancak and vicinity ) is influenced by the tide . The slope of the river estuary is very gentle with the deposition of sediments in the estuary level is relatively high .Research materials are mostly primary data are searched directly in the research area and equipped with relevant secondary data from the last 5 years of data. Sowan river basin area 205,818 km2 , with rainfall in the basin is about 1,900 mm per year . Kondition for environmental water quality in the river mouth area Sowan obtained Perancak beach water quality data obtained magnitude BOD levels 10.61 mg / l and COD levels of 16.47 mg / l . Watershed wide Badung of 52,497 km2, land conditions in  the estuary area of Badung in Denpasar . Land use changes that often occur lately triggered sedimentation / siltation in the river cross-sectional area and also increase the discharge capacity of the body into the river so that it will increase the risk of flooding. Tukad Badung Denpasar flow splitting , 19,601 km river length,  with headwaters located 12 km to the north of Denpasar and empties into the Gulf of Benoa , an important source of raw water for the city of Denpasar and southern Badung regency.
Keywords: estuary , land , river , raw water